Predation and epibiosis on egg capsules of the Shorttail fanskate, Sympterygia brevicaudata - Seguel, Mylene E.; Ramírez-Rivera, Sebastián; Concha, Francisco; Espinoza, Mario; Hernández, Sebastián (Revista de Biología Marina y Oceanografía, 2022)
After deposition, chondrichthyan egg capsules are frequently exposed to numerous threats that affect their survival. However, the ecological factors affecting the development and survival of embryos inside egg capsules remain unclear. The aims of this study was to quantify and describe two ecological factors that affect of the Shorttail fanskate Sympterygia brevicaudata egg capsules: predation and epibiosis. The egg capsules were collected (241) stranded from Coquimbo Bay’s intertidal zone in northern Chile (29°57’S; 71°18’W and 71°19’W), and examined predation marks and epibiosis of these egg capsules at different stages of development. About 32.8% of the egg capsules presented evidence of predation marks, of which 48.1% had not yet hatched. Based on our findings, the shape and size of predation marks were different from those reported in the literature. Additionally, 78% of the egg capsules presented epibiosis, of which 21% had not yet hatched. Non-hatched egg capsules with more advanced stages of development (i.e., possessing open respiratory fissures) showed a higher probability to be predated and present epibiosis than those with earlier development (closed respiratory fissures). Ecological interactions, such as predation and the settlement of epibionts, may influence demographic aspects such as hatching success and survival rate, regulating the population sizes of S. brevicaudata during the embryonic phase.